Progress in implementing the ecosystem approach to fisheries in South Africa in principle and in practice - Duna, Elethu Zamandlane Lona (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2017)
Over the last century, the population of the world has more than doubled, resulting in an increase in seafood consumption (FAO 2010), and placing strain on fisheries wild stocks, their habitats, and the coastal communities that rely on them for food and survival. The ecosystem approach to fisheries (EAF) differs from other management approaches by combining all aspects of ecosystem management, and strives to conserve ecosystem structure, maintain diversity, productivity, and integrity, and to meet human food and economic needs. This study aims to assess how South Africa is progressing in implementing EAF in principle and in practice, to identify challenges, and suggest solutions, where appropriate. The law sets precedence on governance. An assessment of the Marine Living Resources Act, (MLRA) and the South African Policy for Small-scale Fisheries (SSFP) revealed that, although these instruments recognise and contain elements of EAF, this management approach has not been adequately implemented. In practice, the status of implementation of EAF was assessed through the Southern African Sustainable Seafood Initiative (SASSI) and the Ecological Risk Assessments (ERA). The scores of 65 assessments, conducted in 2013 and 2014, were obtained from SASSI. Of the 65 species assessed; 18.4% were listed as Green, 50.8% were listed as Orange and 30.8% were listed as Red. Two methods were used to analyse the data; non-metric multidimensional scaling (NMDS), and cluster analysis in the statistical program R. Analysis of the SASSI assessments indicates that there has been progress in implementing EAF since the World Summit on Sustainable Development in 2002. The high number of Orange and Red listed species however, indicate that major sustainability issues still exist. Species in commercially important fisheries enjoy the bulk of research and management attention compared to other species, including bycatch species, as reflected by a high proportion of Green-rated commercially important species. Based on these results, four fisheries were chosen for further indepth analysis using additional information found in ecological risk assessments: offshore demersal trawl, inshore demersal trawl, West Coast rock lobster fishery and the line fishery. The documents and published literature of the Department of Agriculture, Forestry and Fisheries Internal Scientific Working Groups provided further information. A Wilcoxon signed rank test conducted in the programme R on the results of the ERAs showed that there was a decline in implementation of EAF and reinforced the earlier conclusion that large commercial fisheries, offshore and inshore demersal trawl, were progressing in implementing EAF faster than West Coast rock lobster and line fisheries, which are examples of smaller-scale fisheries that are more accessible to many resource users. Both progress and challenges appeared to be largely influenced by several common factors, which include the presence or absence of positive incentives, co-management, management plans, access, compliance, economic importance, capacity, and the interests of rights holders and other stakeholders.
Keywords: Fisheries -- Environmental aspects -- South Africa; Sustainable fisheries -- South Africa; Fishery management -- South Africa; South African Sustainable Seafood Initiative